بلوغ المرام از حافظ ابن حجر عسقلانی : اسالیب و ترتیب اور درجہ بندی کا تحقیقی جائزہ - Ismail, Hafiz Asif; Yousaf, Umer (Mujalla Islami Fikr-o-Tahzeeb (MIFT) / مجلہ اسلامی فکر و تہذیب, 2024)
Bulugh al-Maram" by Hafiz Ibn Hajar al-Asqalani is a renowned and authoritative work that organizes Islamic legal issues in light of Prophetic traditions. This study aims to explore the methodology, organization, and classification employed by the author. Hafiz Ibn Hajar meticulously categorized hadiths into various chapters, ensuring clarity and removing ambiguities by presenting multiple chains of transmission. This approach aids readers in comprehending the depth of legal matters and understanding the precise meanings of the hadiths. The research will delve into the principles of categorization and classification to highlight the scholarly and methodological aspects of "Bulugh al-Maram.